Markets for Sustainable Resource Use: Auctioned Limited-Tenure Use Rights with Refunding - Ralph Winkler; Martin Quaas (Verein für Socialpolitik, 2010)
Efficiency and sustainability often clash if limited-tenure use rights for renewable natural resources are rented to private resource managers. We introduce a mechanism reconciling these two issues for a stochastically developing natural resource. The mechanism selects the most patient and, thus, most sustainably harvesting resource manager in a second-price sealed-bid auction with minimum bids and it overcomes the incentive to mine the resource at the end of tenure by announcing a refund if a sustainability goal is obeyed. In addition, the mechanism ensures efficiency and is self-financing in expectation.
Keywords: Q20; D44; D82; 330; auctioning-refunding-mechanism; efficiency; renewable resource; stochastic model; sustainability